Implications of hydrodynamics on the design of pulsed sieve-plate extraction columns: A one-fluid multiphase CFD model using the volume of fluid method. (10th August 2020) - Theobald, Daniel W.; Hanson, Bruce; Fairweather, Michael; Heggs, Peter J.
Highlights: LES was successful in capturing time-dependent hydrodynamics of PSEC geometry. Overall time-invariant flow behaviour despite sinusoidal boundary conditions. Turbulence was found to be the principal factor driving dispersive mixing. Classic sieve-plate design performs poorly in producing efficient turbulent flow. Abstract: Presented is a detailed assessment of dispersive mixing and turbulence characterisation of an industrially representative pulsed sieve-plate extraction column (PSEC) obtained using multiphase CFD modelling. The system consists of a 150 mm diameter column with two perforated plates dispersing a 30 vol% dodecane/tributyl phosphate mixture in 3 M nitric acid. Operational conditions were chosen to examine pseudo steady-state dispersion regime operation. Three-dimensional transient flow calculations were performed using large eddy simulation (LES), coupled with the volume of fluid method. This study finds that LES is effective at capturing the different scales of turbulence present within PSECs, and their operational influence. Explicit analysis of the hydrodynamics established that the sieve-plates drive dispersive mixing through their influence on the resulting turbulent flow and flow structures. Furthermore, the standard round-hole sieve-plate design is found to perform poorly at producing and distributing the types of flow and turbulence beneficial to droplet size reduction.